Pengaruh Parakuat terhadap Produksi Hidrogen Peroksida secara Fotokimia dalam Kloroplas Daun Bayam (Spinacia oleraceae L.) - Paini Sri Widyawati (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2002)
The phytotoxicity of paraquat was suggested due to the production of toxic superoxide during the interaction of paraquat and photosystem l, on the other hand it is also suggested that the paraquat free radical itself is the toxicant. In this study, the effect of paraquat in the production of hydrogen peroxide in chloroplast of spinach leaves (Spinacia oleraceae L.), which is formed form superoxide in the presence of superoxide dismutase and water, was investigated under the influence of irradiation time, amount of oxygen and pH. The result showed that hydrogen peroxide was produced even if there is no paraquat added, meaning that the enzymes activity, such as superoxide dismutase, ascorbate peroxidase, dehydroascorbate reductase and glutathione reductase, cancelled the phytotoxicity of hydrogen peroxide production increases as paraquat is added, the irradiation time and the amount of oxygen present increases. The optimum pH for hydrogen peroxide production was 8. Further study using supernatant, chloroplast pellet and both supernatant and chloroplast pellet, showed that paraquat was acting as electron acceptor for electrons generated by photosystem l and catalyzing the hydrogen peroxide production. This result explain the desiccant effect of paraquat.